Environmental friendly maize (Zea mays L.) production on chernozem soil in Hungary - Pepó, Péter (Acta Agraria Debreceniensis, 2010)
We have been studied the effects of crop-rotation, fertilization and irrigation on the yields of maize in different cropyears characterizedby different water supply (2007 year=dry; 2008 year=optimum) on chernozem soil. Our scientific results proved that in water stresscropyear (2007) the maximum yields of maize were 4316 kg ha-1 (monoculture), 7706 kg ha-1 (biculture), 7998 kg ha-1 (triculture) in nonirrigated circumstances and 8586 kg ha-1, 10 970 kg ha-1, 10 679 kg ha-1 in irrigated treatment, respectively. In dry cropyear (2007) theyield-surpluses of irrigation were 4270 kg ha-1 (mono), 3264 kg ha-1 (bi), 2681 kg ha-1 (tri), respectively. In optimum water supply cropyear(2008) the maximum yields of maize were 13 729-13 787 (mono), 14 137-14 152 kg ha-1 (bi), 13 987-14 180 kg ha-1 (tri) so there was nocrop-rotation effect. In water stress cropyear (2007) fertilization caused yield depression in non irrigated treatment (control=2685 kg ha-1;N240+PK=2487 kg ha-1). Our scientific results proved that the effects of abiotic stress could be strongly reduced by using the optimum cropmodels in maize production. We obtained 8,6-11,0 t ha-1 maximum yields of maize in water stress cropyear and 13,7-14,2 t ha-1 in optimumcropyear on chernozem soil with using appropriate agrotechnical elements.